Cultures in Mountain Areas / Culture in aree di montagna / Kulturen in Gebirgsregionen Comparative Perspectives / Prospettive comparative / Vergleichende Perspektiven - Albera, Dionigi (bu,press, 2022)
Comparative studies of mountain areas have long been at the core of the discussion about the relations between nature and culture as well as on environmental and social change. This volume searches for ways to develop further critical comparative perspectives in the study of cultures in mountain areas by drawing inter- and transdisciplinary links amongst anthropology, geography, folklore studies, montology, and global history. Drawing on examples mostly from the Alps and the Andes, but also extending to the global mountains, the authors explore socioecological environments, historical and political processes, borderscapes, demographic dynamics, forms of domestic organization, rituals, religiosities, and human-non-humanrelations.